Clinical characteristics and microbiology of nosocomial enterococcal bloodstream infections in a tertiary-level hospital: a retrospective study, 2007–2019. (April 2022) - Dai, Z.; Chen, L.Y.; Cai, M.J.; Yao, Y.H.; Zhu, J.H.; Fang, L.L.; Tang, R.; Liang, X.M.
Summary: Background: Enterococci are important pathogens causing nosocomial bloodstream infections (BSIs) and cannot be treated with appropriate timely empirical antibiotics due to their natural resistance to many kinds of antibiotics. Aim: To analyse the clinical characteristics and microbiological features of nosocomial bloodstream infections caused by enterococci. Methods: The clinical characteristics and microbiological features of nosocomial enterococcal BSI patients in Xiamen University Zhongshan Hospital were examined in a case-controlled retrospective study. All patient information was collected through an electronic surveillance system. Findings: A total of 199 cases were identified as nosocomial enterococcal BSIs over a period of 13 years. The incidence of BSIs fluctuated from 0.21% to 0.81%. In the distribution of wards, enterococcal BSIs in hepatobiliary surgery ranked first. Intra-abdominal diseases (odds ratio: 3.36; 95% confidence interval: 2.15–5.27; P < 0.001), chemotherapy history (4.37; 2.06–9.25; P < 0.001), and urinary catheterization (2.34; 1.52–3.61; P < 0.001) were risk factors for nosocomial enterococcal BSI acquisition. Vancomycin-resistant enterococci and linezolid-insensitive enterococci strains were not found. Conclusion: Patients with a history of intra-abdominal disease, chemotherapy and urinary catheterization are at higher risk of nosocomial enterococcal bloodstream infections. The enterococcus strains were still sensitive to commonly used antibiotics.